2019
DOI: 10.1039/c8re00226f
|View full text |Cite
|
Sign up to set email alerts
|

Origins of complex solvent effects on chemical reactivity and computational tools to investigate them: a review

Abstract: Origins of solvent-induced enhancement in catalytic reactivity and product selectivity are discussed with computational methods to study them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
147
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 194 publications
3
147
0
1
Order By: Relevance
“…functional groups held in specific spatial orientations, or functional group dissections that do not exist). Similarly, the computational prediction of solvent effects remains notoriously difficult . Therefore, for our experimental investigations in solution, we instead sought model systems in which through‐space effects would dominate over those occurring through bonds.…”
Section: Resultsmentioning
confidence: 99%
“…functional groups held in specific spatial orientations, or functional group dissections that do not exist). Similarly, the computational prediction of solvent effects remains notoriously difficult . Therefore, for our experimental investigations in solution, we instead sought model systems in which through‐space effects would dominate over those occurring through bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that these effects are significant, for example, ORR on the Pt (111) surface and single‐atom catalyst . First‐principles molecular dynamics simulations with explicit water molecules are often used to obtain the water‐adsorbate interactions and/or the reaction barriers . However, this approach often suffers from high computational cost and large statistical error bar which can be comparable to the interaction energetics .…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Whilst the Kamlet and Taft parameters provide a good general and qualitative description for solvent effects, experimental measurements able to reveal physico‐chemical insights at a molecular level in solvent‐based homogeneous catalytic processes have remained overlooked. Computational tools can be used to explain solvent effects in catalysis . Experimental tools are however essential and, among the potential techniques for experimental studies of solvent effects in homogeneous catalysis, nuclear magnetic resonance (NMR) measurements of diffusion coefficients represent a powerful, non‐invasive method for studying interactions in homogeneously catalysed chemical reactions.…”
Section: Introductionmentioning
confidence: 99%